A Mixed Porphyrin–Schiff Base Dysprosium(III) Single‐Molecule Magnet. Issue 26 (16th August 2016) - Ma, Qi; Zeng, Suyuan; Feng, Xuenan; Cao, Wei; Wang, Hailong; Dou, Jianmin; Jiang, Jianzhuang
Abstract : The mixed porphyrin–Schiff base potassium dysprosium(III) complex [K(TBPP)Dy(L)(CH3 CN)2 ] [H2 TBPP = 5, 10, 15, 20‐tetrakis(4‐ tert ‐butylphenyl)porphyrin; H2 L = N, N′ ‐bis(3‐methoxysalicylidene)benzene‐1, 2‐diamine;1 ] was isolated from the reaction between the metal‐free Schiff base ligand H2 L and the half‐sandwich porphyrinato dysprosium compound [Dy(TBPP)(acac)] (Hacac = acetylacetone) in the presence of KOH. A sandwich‐type double‐decker structure has been unambiguously revealed by single‐crystal X‐ray diffraction analysis. Static and dynamic magnetic measurements disclosed the slow relaxation behavior of this new double‐decker compound and indicated its single‐molecule magnet (SMM) nature. Comparative studies on the magnetic properties of1, the homoleptic bis[5, 10, 15, 20‐tetrakis(4‐ tert ‐butylphenyl)porphyrinato]dysprosium double‐decker [DyH(TBPP)2 ] (2 ), and the bis(Schiff base)dysprosium double‐decker [Dy[Zn(L)Cl]2 (DMF)2 ]· Cl (3, DMF = N, N ‐dimethylformamide) indicate the effect of the ligand field (LF), through the deviation of the dysprosium coordination geometry from the ideal D 4 d form, on the SMM properties of1 –3 in addition to the effect of the charge distribution over the Dy III ion. Abstract : A mixed porphyrinato–Schiff base potassium dysprosium(III) double‐decker single‐molecule magnet is synthesized and structurally characterized for the first time.